GAZÂLİ'DE SİYASET DÜŞÜNCESİ - ŞEKER, KENAN (Fırat Üniveristesi, 2008)
Gazali İslam düşünce tarihinde en çok tartışılan ve üzerinde en çok çalışma yapılan şahsiyetlerin başında gelir. Bir şahıs üzerinde çalışırken, onun yaşadığı devirdeki siyasi arka plan görmezden gelinemez. Oldukça karışık ve buhranlı bir coğrafyada yaşayan Gazali, yaşadığı dönemin siyasi gelişmelerinden etkilenmiştir. Zamanının siyasi gelişmelerinden etkilenen Gazali'nin devlet başkanlığı konusundaki görüşlerini teorik ve pratik açıdan ele almaya çalıştık.Çalışmanın giriş bölümünde Gazali'nin siyasi arka planını ele alarak, onun siyasetle ilgili eserlerini incelemeye çalıştık. Birinci bölümde Gazali'nin siyaset düşüncesi doğrultusunda, devlet başkanlığı meselesine teorik bakışını vermeye çalıştık. İkinci bölümde ise, onun devlet başkanlığına dair pratik görüşlerini ele aldık, sonuç bölümünde kısa bir değerlendirme yaparak çalışmamızı tamamladık.

Ghazali is one of the foremost personalities who has been discussed on and studied most in the History of Islamic Philosophy. While wo?rking on somebody, the political affairs occuring at the time of the person should be taken into consideration. Ghazali who lived in a very troubling and disordered geography, was affected by the political affairs coming out at his time. We have tried to touch on Ghazali?s ideas on the state presidency, those were affected by the political changes of his time, theoritically and practically.In the introduction part of the thesis, we have tried to study on Ghazali?s works on policy through dealing with his political background. In the first part , we have tried to present Ghazali?s theoretical point of view to the issue of state presidency through his political thought. In the second part, we have tried to explain his political ideas on the state presidency, and in the conclusion part, we have finished our work with a brief sum of the thesis.
Ghazali?s political thoughts
Keywords: Din